Productivity Measurement Analysis of the Garment Industry Using the Objective Matrix (OMAX) Method - Kartika sari, Ukik; Nugrahadi, Bekti (Universitas Mercu Buana, 2023)
Companies are increasingly realizing the importance of managing Human Resources (HR) to enhance organizational effectiveness and efficiency. Various efforts have been made to retain employees, including psychological approaches involving motivation, perception, learning, beliefs, and attitudes. Productivity is a key factor in maintaining a company's existence and improving its competitiveness. Productivity measurement can be done through three basic forms: partial productivity, total factor productivity, and total productivity. The research method employed in this paper is a qualitative-quantitative approach, utilizing the Objective Matrix (OMAX) as the productivity measurement method. OMAX involves identifying relevant performance indicators, assigning weights to each indicator, and scoring the evaluated performance indicators. These scores are used to generate an overall productivity index. The findings of this study reveal that OMAX was used to measure productivity from January to April. The research results indicate an increase in productivity in January and February, but a significant decline in April. Further research is needed to identify the causes of this decline and find appropriate solutions to enhance company productivity. The conclusion of this research provides insights into the importance of continuous analysis and improvement to enhance company productivity.